Sistem Digital Pencatatan Berbasis Buku Kesehatan Ibu dan Anak (KIA) untuk Pencegahan Dini Risiko Mortalitas Maternal dan Neonatal: Sebuah Systematic Literature Review - Vitania Mutiara Sari Siregar; Martha Irene Kartasurya; Cahya Tri Purnami (Jurnal Ners, 2026)
Child Health (MCH) Handbook (Buku KIA) has long been used as a manual recording tool, but limitations in accuracy, continuity, and data integration hinder effective monitoring and early detection of complications. Digitalization of the MCH Handbook is considered an innovative solution to strengthen preventive strategies and support data-driven health policies. Objective This study aims to map and analyze literature on the implementation of digital MCH Handbook systems and to identify trends, challenges, and opportunities in reducing maternal and neonatal mortality. Method The study employed a scoping review approach with systematic stages based on the PRISMA framework. A total of 10–13 selected journals using keywords related to addressed digital maternal and child health records. Results Integration with mobile applications and telemedicine supports family education and early detection of complications. Key challenges include limited infrastructure, low digital literacy among health workers and communities, and data security concerns. Government policy support, training, and community engagement are critical for successful implementation. Conclusion Despite challenges, opportunities are substantial, particularly in strengthening continuity of care, supporting health policy, and improving digital literacy. Comprehensive, adaptive, and evidence-based strategies are essential to ensure sustainable success in Indonesia. Keywords: Maternal and Child Health Handbook, digitalization, maternal mortality, neonatal mortality, health information system, systematic review.